The contribution of knowledge and technology in driving change The Algerian University as a model - هبال عبد المالم هبال عبد المالم; عبد الرزاق براهيمي (Milev Journal of Research and Studies, 2018)
This paper aims to demonstrate the importance of the knowledge dimension in facilitating the task of change leaders in the organization as organizational change is an inherent characteristic of all organizations, an important part of the administrative process and a major function of the successful leader, not a reaction that appears only during critical circumstances and crises. Therefore, the administrative leaders face great responsibilities in how to move and motivate the process of change and confront the forces that resist it in all organizations of different levels and diversity of functions, where the world is witnessing various political and cultural changes and changes, economic and social, which was accompanied by crises, political and military conflicts, The ability to predict the future and focus on the Algerian University as a model